Bank credit, expected inflation rate, and financial dynamics - Toshio Watanabe (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2025)
We investigate the effects of debt-capital ratio and expected inflation rate on the stability of the economy using a Minsky model and reconsidering Fisher's debt-deflation theory. We have developed static and dynamic models that formalize an inflation-targeting policy. The static model reveals that an increase in the debt-capital ratio may negatively impact the profit rate and that the Fisher proposition is invalid. Our dynamic model indicates that the economy can become endogenously unstable. When the debt-capital ratio is high and the sensitivity of nominal wage rate to the profit rate is higher than that of bank lending, it may lead to debt-deflation. Finally, we demonstrate that the central bank alone can make only a limited contribution to economic stability.
Keywords: E12; E44; E52; 330; financial instability hypothesis; debt-deflation theory; bank behavior; portfolio selection; inflation-targeting policy